Yogi or fireball – or both – a diary study on the interaction between mindfulness and vigor on job performance - Blume, Johanna Barbara; Dettmers, Jan (Frontiers in Psychology, 2024)
Introduction Building upon the conservation of resources theory and the episodic process model of performance, this research addresses the gap in understanding how daily variations in two personal resources, particularly their interaction, affect job performance. Specifically, this study examines the influence of vigor and mindfulness on daily fluctuations in task performance considering the potential compensation effect between these personal resources in the workplace. Methods We conducted a five-day online diary study involving 192 participants (926 daily observations). At the conclusion of each workday, participants were asked to assess their level of mindfulness and vigor in the workplace using validated scales, as well as estimate their task performance. Results Multilevel analyses showed that both daily mindfulness and daily vigor positively predict self-reported task performance. The interaction between mindfulness and vigor was significant. The results suggest that high levels of mindfulness can compensate for low levels of vigor, and vice versa. Discussion Exploring the interplay of personal resources at work provides a valuable starting point for individual-tailored interventions that enable individuals to reach their full potential. Enhancing employees’ mindfulness may increase job performance directly and empowers workers to compensate for periods of low energy.